Unauthorized Sale of Motorcycles with Outstanding Installments: A DSN-MUI Fatwa and Maslahah Mursalah Analysis - Dimas Muhammad Hanief Arkaan; Ahmad Imam Hambali; Dessy Asnita; Warda Said; Muhammad Dakhlan Gazali (Al-Hiwalah: Journal of Sharia Economic Law, 2026)
The sale and purchase of motorcycles with bad credit is a transaction that does not include the Motor Vehicle Owner's Book (BPKB), commonly known as buying and selling motorcycles with only STNK standards. A small group of Muslims in Surakarta practice this to combat usury and follow the teachings of amar ma'ruf nahi munkar. The goal is to protect small communities (debtors), which are often treated unfairly by debt collectors who violate legal procedures. In response to this behavior, members of the Muslim community formed an anti-usury movement with the aim of abolishing the usury system. This system includes the application of interest on loans and penalties for late payment. The target of this practice is the lender or leasing company, which occurs when the debtor intentionally stops paying credit installments on the motorcycle purchased through leasing and then sells it to another party without the knowledge of the leasing company. The aim of this study is to investigate the purchase and sale of bad credit motorcycles in Surakarta city with reference to the Fatwa DSN and relevant positive laws. The research conducted is descriptive and qualitative and utilizes a sociological approach. The data were collected through observation, interviews, and documentation. The results indicate that the sale and purchase of motorcycles with bad credit in Surakarta violates several rules, as reviewed by the National Sharia Council Fatwa. The buying and selling of motorcycles with bad credit involves the transaction of goods owned by others, which scholars refer to as a fudhulli transaction. However, in Surakarta, the sale and purchase of motorcycles include an element that can harm the contract, namely, the borrower's negative intention to default on payment. This goes against the principles of mashlahah walmursalah.